Aggression : the origin of Germany's war machine - Lehmann-Russbüldt, Otto (Londen: Hutchinson & Co.; New York; Melbourne, 1942)
"by Otto Lehmann-Russbueldt ; with an appendix by Hans Aktuhn on Germany's secret air rearmament 1919-1933 ; preface by Rennie Smith Bibliotheek Camille Huysmans"